TASK-BASED LANGUAGE TEACHING FOR ENHANCING STUDENTS’ SPEAKING ABILITY IN JUNIOR HIGH SCHOOL - Selvia Meyra Nugrahaeni (Globish: An English-Indonesian Journal for English, Education, and Culture, 2022)
This study aimed to determine whether the application of TBLT in learning English can improve students' speaking skills. This research was conducted in one of the Junior High Schools in Magetan with the participation of 16 students in second grade and an English teacher. This study used pre-experimental research with one group pre-test- post-test design. The researcher used observations and interviews with the teacher to collect data and conducted tests (pre-test and post-test) on students as the research instruments. SPSS statistic was used to analyze the data, in particular using the paired sample test. The average value of the post-test was (85.25), which was higher than the mean score of the pre-test (60.25). The t-test score is -25,000 and the degree of freedom (df) is 15. Thus, it could be concluded that the implementation of TBLT may help students enhance their speaking skills.